Human Visual Intelligence-based Multi-Modal Multi-Dimensional Analytics for Metaverse and First-Responder Technology - Rajeev, Srijith. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Electrical Engineering.; Advisor: Karen Panetta.; Committee: Sos Agaian, Ronald Lasser, and James Intriligator.; Keywords: Artificial intelligence, and Computer science.